Non-specific immune responses of the Indian major carp Labeo rohita Hamilton to infestation by the freshwater fish louse Argulus siamensis (Wilson) - Shailesh, Saurabh; Sahoo, P K (Indian Journal of Fisheries, 2016)
The study was undertaken to evaluate the non-specific immune responses of the Indian major carp, Labeo rohita naturallyinfested with different loads of the freshwater fish louse, Argulus siamensis. Results showed that glucose level and totalantiprotease activity of serum were significantly higher in fish with different degrees of lice infestation, compared to uninfestedcontrol fish. Complement and Î±-2 macroglobulin activities were significantly (p